Add-on Antidepressants in the Naturalistic Treatment of Schizophrenia Spectrum Disorder – When, Who, and How? - Schennach, Rebecca; Obermeier, Michael; Seemüller, Florian; Jäger, Markus; Schmauss, Max; Laux, Gerd; Pfeiffer, Herbert; Naber, Dieter; Schmidt, Lutz G.; Gaebel, Wolfgang; Klosterkötter, Joachim; Heuser, Isabella; Maier, Wolfgang; Lemke, Matthias R.; Rüther, Eckart; Klingberg, Stefan; Gastpar, Markus; Spellmann, Ilja; Musil, Richard; Möller, Hans-Jürgen; Riedel, Michael (Pharmacopsychiatry, 2017)
The aim of this study was to evaluate antidepressant add-on treatment within the acute treatment of schizophrenia spectrum disorder patients. Antidepressant add-on was evaluated in 365 patients within a naturalistic multicenter study. Patients with/without antidepressant add-on were compared regarding clinical and treatment-related variables, response and remission, and remission of depressive and negative symptoms. The efficacy of antidepressant add-on treatment was furthermore analyzed applying marginal structure models. Twenty-three percent of the patients received antidepressant add-on for a mean duration of 50.28 (33.42) days. Patients with the diagnosis of a schizoaffective disorder, multiple illness episodes, and a longer duration of their illness as well as those with significantly fewer baseline positive symptoms, more negative and depressive symptoms, more side effects, and less subjective well-being were augmented with antidepressants. At discharge no significant effect of antidepressant add-on treatment was observed in terms of a 25% improvement (p=0.2623), a 50% improvement (p=0.3946), remission (p=0.0552), or remission of depressive (p=0.6336) and negative symptoms (p=0.8756). Also, when analyzing marginal structure models considering the diagnostic subgroups, no significant effect was found. Add-on with antidepressants is common. A final recommendation in terms of this strategy’s efficacy cannot be given.
Keywords: schizophrenia spectrum disorder; antidepressants; add-on; prescribing pattern; efficacy